New Data on Migration Time, Breeding Phenology, and Breeding Success of European Turtle Doves in Their Highest Breeding Habitats in North Africa - Mansouri, Ismail; Ousaaid, Driss; Squalli, Wafae; El Agy, Abdelbari; EL-Hassani, Abderahim; Mounir, Mohamed; Elghadraoui, Lahsen; Dakki, Mohamed (International Journal of Zoology, 2021)
The migration dates, breeding phenology, and reproductive success of the European turtle doves were studied in the highest breeding habitats at Midelt (1400 to 1600 m), Morocco. Data were recorded from March to October between 2015 and 2018, using the Common Bird Census methodology. Results showed that, at high-altitude breeding sites (n = 20), turtle doves arrived on 28.25 ± 2.05 March, while departure dates were on 28.00 ± 1.47 September. On the other hand, nesting activity began on 26.5 ± 0.64 April, and laying dates were only two days after the nest construction date on 28.00 ± 0.7 April. First fledged chicks were 17.50 ± 2.72 May, and chicks started flying on 3.50 ± 2.33 June. In addition, breeding chronology, including nesting and chick’s flight, was influenced by altitude and rainfall and more particularly controlled by temperature. For breeding success, among the 467 monitored nests, 73.87% survived during the nesting period and 71.16% of eggs have survived during incubation. Chicks' survival rate was higher with 79.56%. Failure factors during breeding success were diverse. Predation caused the loss of 18.89% of eggs during incubation periods and 10.54% of chicks during the nestling phase. A few portions, including 4.41% of eggs and 4.39% of chicks, were deserted by their dove parents. Finally, our study highlights that the turtle dove breeds in high-altitude habitats with late and shorter breeding periods, which might allow this bird to avoid the vigorous climate conditions at mountains and their effect on reproductive success.